Kentish politics and public opinion, 1768-1832 - Humphries, P; Humphries, P. L. (1981)
This thesis seeks to examine the increasing importance of national issues and popular consciousness in the politics of the county of Kent during the late eighteenth and early nineteenth centuries. The Excise and Jew Bill crises indicate that public opinion and extra-parliamentary protest were by no means dormant under the early Hanove.rians, but without effective leadership either at Westminster or in the provinces, without a coherent ideological basis, and without the encouragement of a well-oiled propaganda machine, reaction to national events tended to be unco-ordinated and short-lived. Not until after 1768, when men like Wilkes, Wyvill and John Reeves began to organise popular agitation, when Burke, Paine and Gartwright gave shape to conservative and radical ideas, and when better transport and the development of the press facilitated the easy diffusion of news and comment, did a new complexion come across the face of English affairs. Clearly defined issues also appeared on the politidal stage and quickly cultivated a high level of public debate. Between 1768 and 1783 the Middlesex election dispute and the American War focused the attention of Kent's urban freemen and landed classes on calls for parliamentary and economical reform, and ensured that the county was in the van of those who joined Yorkshire in its campaign of lobbying and petitioning. After 1784 reform was eclipsed, first by the all-embracing struggle among the partisans of Pitt and Fox, and then by the dark menace of Jacobin and Napoleonic France, but in the context of public awareness and participation, the fall of the Coalition and the Regency crisis, together with the formation of Reevite committees, corresponding societies and the Volunteers, gave these turbulent decades a lasting significance. The return to peace in 1815 brought fresh problems for Kentish gentlemen and labourers alike and acted as a spur to renewed agitation out-of-doors. When, however, ministers, and the House of Commons proved deaf to the pleas of a distressed nation, and even went so far as to violate the much acclaimed Protestant Ascendancy, constitutional change seemed the only remaining remedy and by 1832 concerted popular enthusiasm had carried the Reform Bill over every obstacle thrown in its path.